2007
DOI: 10.1152/ajpregu.00057.2007
|View full text |Cite
|
Sign up to set email alerts
|

Use of a novel and highly selective oxytocin receptor antagonist to characterize uterine contractions in the rat

Abstract: Spontaneous and induced uterine contractions in the rat were found to be inhibited by a novel and selective oxytocin receptor antagonist GSK221149A (3R,6R)-3-Indan-2-yl-1-[(1R)-1-(2-methyl-1,3-oxazol-4-yl)-2-morpholin-4-yl-2-oxoethyl]-6-[(1S)-1-methylpropyl]-2,5-piperazinedione. GSK221149A displayed nanomolar affinity (K(i) = 0.65 nM) for human recombinant oxytocin receptors with >1,400-fold selectivity over human V1a, V1b, and V2 receptors. GSK221149A had similar affinity (K(i) = 4.1 nM) and selectivity for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 36 publications
(44 reference statements)
0
26
0
1
Order By: Relevance
“…GSK221149A is greater than 15-fold more potent than atosiban with a far superior selectivity profile with respect to vasopressin receptors. 41 The OTR selectivity for 74 vs. these receptors is 418,000 for hV1a, 415,000 for hV1b, and 41,400 for hV2). A further measure of the potency of our lead OT antagonist 74 was established by its functional OT antagonist activity (fpK i ) in whole cells (by the FLIPR assay 27 ).…”
Section: A Selectivity Vs Human Vasopressin Receptors and Functionamentioning
confidence: 97%
See 2 more Smart Citations
“…GSK221149A is greater than 15-fold more potent than atosiban with a far superior selectivity profile with respect to vasopressin receptors. 41 The OTR selectivity for 74 vs. these receptors is 418,000 for hV1a, 415,000 for hV1b, and 41,400 for hV2). A further measure of the potency of our lead OT antagonist 74 was established by its functional OT antagonist activity (fpK i ) in whole cells (by the FLIPR assay 27 ).…”
Section: A Selectivity Vs Human Vasopressin Receptors and Functionamentioning
confidence: 97%
“…7). 41 Uterine activity was measured as an integral of force Intravenous administration of GSK221149A to late-term pregnant rats significantly reduced spontaneous uterine contractions in a dose-dependent manner (Fig. 8).…”
Section: B In Vivo Potencymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, spontaneous uterine contractions in late-term pregnant rats (at 19-21 days gestation) were significantly reduced by intravenous administration of GSK221149A at a dose of 0.3 mg/kg. In vitro experiments using Chinese hamster ovary (CHO) cell membranes expressing human OT receptors or human V1a, V1b, or V2 receptors, and human endothelial kidney (HEK) cells expressing rat oxytocin receptors showed that GSK221149A also has a higher affinity for human and rat oxytocin receptors than for V1a and V2 receptors (McCafferty et al, 2007). GSK221149A is over 15-fold more potent compared to atosiban for the OTR (Borthwick and Liddle, 2011).…”
Section: Oxytocinmentioning
confidence: 99%
“…Oxytocin OTR (h) COS-7 0.7 OT [25] OTR (h) CHO 0.5 OTA [55] OTR (r) CHO 1.9 OTA [55] V1AR (h) CHO 123 OTA [55] V1AR (r) CHO 120 OTA [30] V1AR (r) COS-7 845 LVA [110] V1BR (h) CHO 1782 OTA [111] V2R (h) CHO 1544 OTA [55] V2R (r) CHO 3500 OTA [30] [Arg 8 ]-vasopressin OTR (h) COS-7 6.5 OT [25] OTR (h) CHO 1.7 OTA [112] OTR (r) CHO 1.7 OTA [112] V1AR (h) CHO 1.1 AVP [112] V1AR (r) CHO 2.6 AVP [112] V1BR (h) CHO 0.7 AVP [112] V1BR (r) CHO 3.3 AVP [112] V2R (h) COS-7 0.6 OT [25] V2R (h) CHO 1.2 AVP [112] V2R (r) CHO 0.5 AVP [112] Carbetocin OTR (h) COS-7 7.1 OT [25] OTR (r) Uterus 2.0 § OT [36] V1AR (r) Uterus 7.2 § AVP [36] V2R (r) Kidney 61.3 § AVP [36] Peptide antagonists OTR (h) Rec Ltk 895 OTA [50] OTR (h) Uterus 775 OTA [50] OTR (h) UtSMC 561 OTA [50] OTR (h) CHO 81 OTA [55] OTR (h) CHO 11 OT [47] OTR (h) HEK293 27 OTA [55] OTR (r) Uterus 215 OTA [50] OTR (r) CHO 76 OTA [55] OTR (r) CHO 32 OT [47] V1AR (h) CHO 0.15 AVP [47] V1AR (r) Liver 1059 AVP [50] V1AR (r) Liver 310 AVP [47] V1BR (h) CHO 44 AVP [47] V1BR (r) CHO 241 AVP [50] V2R (h) CHO 330 AVP [47] V2R (r) Kidney > 1000 AVP [50] V2R (r) Kidney 29 AVP [47] Barusiban OTR (r) Breast 8.9 OT [41] ...…”
Section: Peptide Agonistsmentioning
confidence: 99%